Sexual risk behaviour and its associated factors among university students in Malaysia - Mohamad, Fadzilah; Kamaruddin, Khairatul Nainey; Shibraumalisi, Nur Amirah; Syed Mohamad, Sharifah Najwa; Mohd Azlan, Syifa; Dahlan, Rahima; Ismail, Irmi Zarina; Kadir Shahar, Hayati; Shamsuddin, Nurainul Hana (Springer Nature, 2025)
Introduction: Sexual risk behaviour (SRB) is a high-risk act that often led to many reproductive health psychological related issues. Such behaviour is becoming higher among university students, and this has been one of the major public health concerns worldwide. Objective: The aim of this study was to determine the prevalence of sexual risk behaviour (SRB), and the factors associated to this behaviour among students attending universities in Malaysia. This was a nationwide research study which may serve as a baseline local data which for policy makers to strengthen the current sexual reproductive health intervention and prevention programmes. Methods: A nationwide cross-sectional survey was conducted in 28 universities in Malaysia. Stratified random sampling was applied. It was an online questionnaire that consisted of participants’ socio-demographic background, academic background, substance abuse, history of childhood abuse, religiosity, knowledge on sexuality, attitude on pre-marital sex, parents’ parenting behaviour, peer influence and SRB. Data was analysed using SPSS 29 software. Descriptive statistics were computed for all variables, whereby the association between SRB and variables above were analysed using logistic regression analysis. The level of significance was set at p < 0.05. Results: This study recruited 1172 respondents. The prevalence of SRB among the university students was found to be 7.2%. The respondents’ mean age was 20.16 ± 1.66. Smoking/vaping history (AOR 5.91 (3.49–10.01)), alcohol use (AOR 1.93 (1.10–3.40)), age (AOR: 1.88 (1.14–3.12)), peer pressure (AOR 1.10 (1.04–1.17)), father care (0.96 (0.93–0.99)) and non-organized religious activity (NORA) (AOR 0.72 (0.63–0.84)) were found to be statistically significant. Protective factors were father care and NORA. The higher the father care and NORA, the less likelihood the students would engage in SRB. Conclusion: Prevalence of SRB among university students was 7.2% and the factors associated with SRB were age, smoking status, alcohol use, peer pressure, fathercare and NORA. Preventive plans of such behaviour must be made parallel to the needs of the youth as this generation represents the future of the country.